2009
DOI: 10.1097/olq.0b013e3181a2aab9
|View full text |Cite
|
Sign up to set email alerts
|

The English National Chlamydia Screening Programme: Variations in Positivity in 2007/2008

Abstract: This is the largest description of testing for Chlamydia trachomatis in healthcare and nonhealthcare settings outside Genitourinary Medicine clinics in England and allowed a detailed analysis of positivity by age and ethnic group. Considerable heterogeneity exists and local health service commissioners need to ensure that the implementation of chlamydial screening reflects these differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
3
29
1
Order By: Relevance
“…The differences in the age-related prevalence of chlamydial conjunctivitis by gender have also been observed in other studies (Stenberg & Mårdh, 1990;Postema et al, 1996;Quirke & Cullinane, 2008). Genital chlamydial infections show the same correlations, as some surveillance reports have found that the proportion of diagnosed chlamydial infections varied by gender across the age groups and C. trachomatis was detected more commonly among women than among men in the younger age groups (HPA, 2008;Simms et al, 2009). The disparity in the pattern of positivity between men and women by age may indicate the influence of certain sexual relationships on the transmission of the pathogen, as younger women tend to have older partners (Wadsworth et al, 1996;Johnson et al, 2001).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The differences in the age-related prevalence of chlamydial conjunctivitis by gender have also been observed in other studies (Stenberg & Mårdh, 1990;Postema et al, 1996;Quirke & Cullinane, 2008). Genital chlamydial infections show the same correlations, as some surveillance reports have found that the proportion of diagnosed chlamydial infections varied by gender across the age groups and C. trachomatis was detected more commonly among women than among men in the younger age groups (HPA, 2008;Simms et al, 2009). The disparity in the pattern of positivity between men and women by age may indicate the influence of certain sexual relationships on the transmission of the pathogen, as younger women tend to have older partners (Wadsworth et al, 1996;Johnson et al, 2001).…”
Section: Discussionsupporting
confidence: 66%
“…1). An association between age and prevalence of infection has also been observed in other studies, indicating that younger age is a proven risk factor for genital C. trachomatis infection (HPA, 2008;Simms et al, 2009). The differences in the age-related prevalence of chlamydial conjunctivitis by gender have also been observed in other studies (Stenberg & Mårdh, 1990;Postema et al, 1996;Quirke & Cullinane, 2008).…”
Section: Discussionmentioning
confidence: 50%
“…Men in general are reported to have CT infections at an older age than women [28,29]. The reason could be that (younger) females tend to have sex with older males, as shown in previous studies [30,31].…”
Section: Discussionmentioning
confidence: 89%
“…Instead, the NCSP was set up as an opportunistic programme offering testing and treatment to men and women under the age of 25 years in healthcare and non-healthcare based settings. The proportion of those testing positive through the programme has been higher than the prevalence observed in the general population7 8 and is likely to be influenced by factors associated with who is offered and who accepts chlamydia testing.…”
Section: Introductionmentioning
confidence: 91%